The Efficacy and Safety of CT-P13 as First-line and Subsequent-line Therapy in Patients with Ankylosing Spondylitis: Real-life Data from TURKBIO Cohort - Uslu, Sadettin; Gulle, Semih; Can, Gercek; Senel, Soner; Capar, Sedat; Dalkilic, Huseyin Ediz; Sari, Ismail (Wiley, 2022)
[Abstract Not Available]
Annual Meeting of the American-College-of-Rheumatology (ACR) -- NOV 10-14, 2022 -- Philadelphia, PA